In situ manufacturing and mechanical properties of syntactic foam filled tubes. (5th June 2016) - Taherishargh, M.; Vesenjak, M.; Belova, I.V.; Krstulović-Opara, L.; Murch, G.E.; Fiedler, T.
Abstract: Novel foam filled tubes were manufactured via a highly reproducible and cost effective in situ process. Stainless steel tubes were filled with ultralight porous expanded perlite particles and molten aluminium infiltrated the gaps between these particles. During casting, a ternary intermetallic phase was formed between the liquid aluminium and steel tube as a result of a chemical reaction. Quasi-static uni-axial compression testing was applied on the foam, empty tube, and foam-filled tube samples. Additional samples were subjected to quasi-static and dynamic three-point bending tests. The results of the quasi-static testing indicate that the foam filling improves the energy absorption capacity of tubes by 2.23 and 3.9 times for compressive and bending loading conditions, respectively. The dynamic bending tests indicate that both empty tubes and foam filled tubes exhibit a positive strain rate sensitivity. It is further shown that a larger tube wall thickness increases the energy absorption of both empty and foam-filled tubes. Foam-filling further increases the energy absorption capacity and, more importantly, the energy absorption efficiency. The impact of foam filling is more substantial in the case of tubes with lower thickness. Graphical abstract: Highlights: A packed bed of porous expanded perlite particles inside a steel tube was infiltrated with molten aluminium. Foam filling improves the specific energy absorption of the tubes both in compressive and bending loading conditions. A higher loading rate in bending test increases the load bearing capacity of the empty and foam filled tubes. The intermetallic compound at the interface improves the interaction and load sharing between the foam and the tube.